2015
DOI: 10.1053/j.ajkd.2015.05.024
|View full text |Cite
|
Sign up to set email alerts
|

Hypomagnesemia and Mortality in Incident Hemodialysis Patients

Abstract: Background In the general population, low serum magnesium (Mg) levels are associated with poor outcomes and death. While limited data suggest that low baseline Mg levels may be associated with higher mortality in hemodialysis (HD) patients, the impact of changes in Mg over time is unknown. Study Design We examined the association of time-varying serum Mg levels with all-cause mortality using multivariable time-dependent survival models adjusted for clinical characteristics and other time-varying laboratory m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

12
85
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 70 publications
(102 citation statements)
references
References 50 publications
12
85
2
Order By: Relevance
“…This study included 515 patients, and the mortality risk decreased by 52% with a 1-mg/dL increase in serum Mg levels. Recently, similar findings have been increasingly reported in large-scale studies [33,34,[69][70][71]. Sakaguchi et al examined this relationship using the Japanese National Registry data [69].…”
Section: Mg and Dialysis Therapysupporting
confidence: 54%
See 4 more Smart Citations
“…This study included 515 patients, and the mortality risk decreased by 52% with a 1-mg/dL increase in serum Mg levels. Recently, similar findings have been increasingly reported in large-scale studies [33,34,[69][70][71]. Sakaguchi et al examined this relationship using the Japanese National Registry data [69].…”
Section: Mg and Dialysis Therapysupporting
confidence: 54%
“…In these three studies [69][70][71], the relationship between hypomagnesemia and the mortality risk remained significant after the full adjustments. However, the findings from the USA [33,34] were different. In Lacson's study [33], a linear decline was observed in the risk of all-cause death adjusted for case-mix variables (see Table 2) from the lowest to the highest serum Mg category, with the best survival in the category with the highest serum Mg levels (> 3.04 mg/dL [1.25 mmol/L]).…”
Section: Mg and Dialysis Therapymentioning
confidence: 79%
See 3 more Smart Citations